Relationship between Urinary Liver-Type Fatty Acid-Binding Protein (L-FABP) and Sarcopenia in Spontaneously Diabetic Torii Fatty Rats. (13th January 2020) - Tanabe, Jun; Ogura, Yuji; Kosaki, Keisei; Nagai, Yoshio; Sugaya, Takeshi; Ohata, Keiichi; Watanabe, Shiika; Ichikawa, Daisuke; Inoue, Kazuho; Hoshino, Seiko; Kimura, Kenjiro; Maeda, Seiji; et al.
Abstract : Background . Type 2 diabetes (T2D) is a known risk factor for diabetic kidney disease (DKD) and sarcopenia in older patients. Because there may be an interaction between DKD and sarcopenia, the aim of the present study is to investigate the relationship between urinary levels of liver-type fatty acid-binding protein (L-FABP) and sarcopenia using a novel rat model of T2D. Methods . Male spontaneously diabetic Torii (SDT) fatty rats (n = 5 ) at 16 weeks of age were used as an animal model of T2D. Age- and sex-matched Sprague-Dawley (SD) rats (n = 7 ) were used as controls. Urine samples were obtained from the rats, and muscle strength was evaluated with the use of the forelimb grip test at 16, 20, and 24 weeks of age. Serum, kidney, soleus, and extensor digitorum longus (EDL) muscle samples were collected at 24 weeks of age. Urinary L-FABP levels were measured using dedicated enzyme-linked immunosorbent assays. Results . Increased urinary L-FABP levels, focal glomerular sclerosis, moderate interstitial inflammation and fibrosis, and accumulation of renal oxidative proteins were significantly observed in the SDT fatty rats, compared to the SD rats. Muscle weight, muscle strength, cross-sectional areas of both type I and type IIb muscle fibers, and increasing rate of muscle strength were significantly decreased in the SDT fatty rats compared to the SD rats at 24 weeks. Urinary L-FABP levels at 20 and 24 weeks were significantly negatively correlated with muscle strength. Urinary L-FABP levels at 16 weeks were significantly negatively correlated with the increasing rate of muscle strength. Conclusions . Urinary L-FABP reflects the degree of muscle strength and weight, as well as cross-sectional areas of muscle fibers. Although further clinical study is needed, urinary L-FABP may be useful to monitor the progression of sarcopenia and DKD in T2D patients.